Pengaruh pertumbuhan ekonomi, tingkat kemiskinan pengeluaran pemerintah, pengangguran dan pendapatan asli daerah terhadap indeks pembangunan manusia di Provinsi Jambi - Adib Hauzan; Yulmardi Yulmardi; Hardiani Hardiani (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
This study aims to: 1) To analyze the development of economic growth, poverty rate, government spending, Unemployment, local revenue, and human development index (IPM) in Jambi Province 2000-2019, and 2) To analyze the effect of economic growth, poverty rate, government spending, Unemployment and local revenue to the human development index (HDI) in Jambi Province 2000-2019. The research analysis tool uses multiple linear regression analysis tools. The results showed that the tax effectiveness ratio in Merangin Regency from 2004 to 2019 was in the very effective category with an effectiveness ratio of 108.07 percent. Furthermore, based on the results of multiple linear regression that only the poverty level and government expenditure variables have a significant effect on HDI in Jambi Province. Meanwhile, economic growth, Unemployment, and PAD have no considerable effect on HDI in Jambi Province. Keywords: Economic growth, Poverty rate, Government expenditure, Unemployment